1976
DOI: 10.1055/s-0028-1091632
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence Structure and Personality in Various Types of Physical Handicap in Childhood and Adolescence

Abstract: Intelligence structure and personality were assessed in a sample of 104 physically disabled children of normal intelligence (IQ is greater than or equal to 85). Findings were compared to those of healthy controls matched by age, sex, rank order and number of siblings and socioeconomic status. Physically handicapped children had lower scores in all subtests of a multi-factorial intelligence test. Furthermore five different subgroups of physically disabled children could be discriminated along one factor marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Apparently the cognitive deficiency is associated with the bodily disproportion or handicap rather than with short stature. It appears to be a nonspecific effect that is also observed in other forms of physical handicap [Steinhausen and Wefers, 1976;Wasserman, 19841. Many of our children with achondroplasia had middle ear problems.…”
Section: Discussionmentioning
confidence: 96%
“…Apparently the cognitive deficiency is associated with the bodily disproportion or handicap rather than with short stature. It appears to be a nonspecific effect that is also observed in other forms of physical handicap [Steinhausen and Wefers, 1976;Wasserman, 19841. Many of our children with achondroplasia had middle ear problems.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, the idea that there is a psychosomatic cause for many chronic diseases has also been challenged (Graham, Rutter, Yule & Pless, 1967;Moos, 1979). In contrast there is abundant evidence that cerebral involvement (especially mental retardation), is an important predictor of emotional problems (Rutter et al, 1970;Steinhausen & Wefers, 1976;Breslau & Marshall, 1985;Breslau, 1985), and some evidence that children with sensory impairments may also be at increased risk (Pless & Satterwhite, 1975a;Pless, 1984a,b). Rutter et al 's (1970) analysis ofthe Isle of Wight survey data appears to have been the first to focus on the distinction between disorders that involve the brain and those that do not.…”
Section: Type Of Diseasementioning
confidence: 99%
“…Studies assessing psychological profiles of GH-IGF-1 deficient/resistant humans and rodents have reported levels of intellectual capability varying from mental retardation to exceptional performance (Laron 1999;Meyer-Bahlburg et al 1978;Sartorio et al 1986;Frankel and Laron 1968;Galatzer et al 1993;Kinney et al 2001a,b;Kinney-Forshee et al 2004). Drotar et al (1980) reported that GH deficient children were ineffective at problem-solving, while other studies have reported deficits in spatial orientation and visual motor integration Stahnke 1976, 1977;Steinhausen and Wefers 1976;Abbot et al 1982). Interestingly, many studies have reported normal intelligence and normal-to-good scholastic achievement for GH deficient/resistant children (Frisch et al 1990;Holmes et al 1984;Dean et al 1985;Sartorio et al 1986;Ranke 1987;Galatzer et al 1987;Kranzler et al 1998).…”
mentioning
confidence: 99%